Bhāratanī ekatā : Paṇḍita Javāharalāla Neharunā, the unity of India, tathā bījā lekhono anuvāda - Nehru, Jawaharlal, 1889-1964 (SAMP early 20th-century Indian books project ;, 1946)
Translation of articles on nationalism.